INFLUENCE OF SILICON WAFER CRYSTALLOGRAPHIC ORIENTATION ON ANODIZATION MECHANISM - N. L. Grevtsov; A. V. Klimenka; A. D. Hurbo; V. P. Bondarenko (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2020)
The influence of silicon wafer crystallographic orientation on the formation of porous silicon during anodization in an HF solution is studied. Cross-section SEM image comparison of samples with different crystallographic orientations has shown that (111) Si samples exhibit a more branching, tree-like pore structure with a higher porosity value compared to (100) Si samples. This phenomenon is explained by pointing out differences in crystal structure and numbers of Si-Si chemical bonds in different crystallographic directions. Namely, in (100)-oriented silicon crystals every surface Si atom has two bonds connecting it to atoms underneath it, as well as two broken bonds able to interact with Fions. Through electron injection into silicon, enough energy is applied to break the underlying bonds, forming SiF as a result. The presence of two Fions bonded with every surface silicon atom leads to weakening the bonds of surface silicon atoms with the underlying atoms, thus making the process of breaking the Si-Si bonds more energy efficient. As for (111)-oriented crystals, silicon atoms only have one broken surface bond, and breaking backbonds with underlying silicon atoms requires a higher value of activation energy due to their larger amount (three as opposed to two for (100) silicon). It is concluded that this very reason leads to slower etching speeds of (111)-oriented silicon wafers. The results help evaluate the way the silicon crystal structure affects the etching process, including its speed and direction, which is an especially important factor to consider when forming (111)-oriented porous silicon.